The inter-individual relationship between training status and activity pattern during small-sided and full-sized games in professional male football players - Rago, V.; Silva, J. R.; Mohr, M.; Barreira, D.; Krustrup, P.; Rebelo, A. N. (Science and Medicine in Football, 2018)
Objectives: We analysed the inter-individual relationship between training status and activity pattern in small-sided games (SSG) and full-sized games (FG). Methods: Fourteen Italian elite male senior football players were monitored during four training sessions incorporating SSG, and six FG, during the pre-season. Baseline measurements included, countermovement jump (CMJ), 5-m sprint time and Yo-Yo intermittent recovery test level 1 distance (YYIR1). Activity pattern was collected via 15-Hz global positioning system with 100-Hz accelerometer integrated. Results: Maximum accelerations (Accmax) and maximum decelerations (Decmax) showed moderate correlations (P < 0.05; r = 0.49 and 0.52) between SSG and FG. YYIR1 correlated with total distance covered (TD) in both SSG and FG (P < 0.05; r = 0.42 to 0.57) and with high-intensity distance (HIR) during FG (P < 0.05; r = 0.46 ± 0.38). CMJ showed positive correlations with TD, Accmax, Decmax, total accelerations (Acctot) and total decelerations (Dectot) during FG (P < 0.05; r = 0.40 ± 0.38, 0.41 ± 0.40, 0.46 ± 0.38, 0.65 ± 0.29, 0.57 ± 0.33). Multiple regression analysis revealed Decmax during SSG, as significant predictor of physical performance during FG, explaining a significant amount of variation in HIR, very-high speed running, Accmax and Decmax (P < 0.05; R2 = 0.49, 0.44, 0.26 and 0.49) during FG. Conclusions: SSG seems more effective to enhance muscular efforts occurring during FG, such as accelerations and decelerations, rather than speed patterns. Specifically, Decmax distance imposed during SSG was identified as the predictor of players` movement patterns during FG. Thus, importance of eccentric strength (i.e. imposed when decelerating) to achieve football-specific fitness is emphasised. These findings may assist coaches and any football practitioners for pre-season programming.